2F.003 30-year analysis of designated international safe communities. (14th March 2021) - Hanson, Dale
Abstract : Background: The International Safe Communities movement was established in 1986. It developed into an international collaborative network comprised of the WHO CCCSP/ISCCC, regional and national safe community organisations, support centres and communities. Purpose: To review the outcomes of communities who have achieved designation as an international safe community over the 32-year period from 1986 to 2018 Method: An audit of the ISCCC database and website was undertaken. Any inconsistencies were checked for accuracy against the original designation application. Results: Since the safe community movement began in 1998 four hundred and three International Safe Communities have been designated. Data was available regarding 361 communities. The program has a high reach, 86 million people have been served by a safe community program that has achieved International Safe Community Designation. Forty-nine million of these are served by safe community programs whose certification remains active. In 2018 there were 39 certifications (13 designations and 26 re-designations), covering a population of 7.1 million people. Conclusion: The International Safe Community movement has accomplished remarkable growth in the 30 years since it began in Sweden in the late 1980s. The program has achieved high reach. Four hundred and three communities have been designated by the end of 2018 with a population footprint of 86 million people.